Kazakhstan-European cultural contacts (Journal of history, 2020)
This article analyzes the humanitarian ties between Kazakhstan and European states, including Germany,Great Britain, and France. After having independence, our Republic conducts its ownpolicy withdifferent countries of the international community, contributing to the integration of the cultural spaceof the peoples of different regions. The relevance of this article is determined by the need to study thecultural processes between the Republic of Kazakhstan and the EU, aimed at cooperation in this sphere,the preservation of cultural heritage and the maintenance of the necessary level of intercultural communication.The dialogue of cultures is constantly improving, acquiring new forms and content. Cultureplays a unifying role through concerts, theatrical performances and decades throw which leads to therapprochement of peoples. A “living bridge” between citizens of the Republic of Kazakhstan and the EUis actively operating, forming a solid basis for promoting cultural and humanitarian ties. Days of cultureof Kazakhstan in different countries, decades of cinema, various festivals are held.